Dibenzofuran-induced mitochondrial dysfunction: Interaction with ANT carrier - Duarte, F. V. (2013)
Exposure to environmental pollutants such as dibenzofurans and furans is linked to the pathophysiology of several diseases. Dibenzofuran (DBF) is listed as a pollutant of concern due to its persistence in the environment, bioaccumulation and toxicity to humans, being associated with the development of lung diseases and cancers, due to its extremely toxic properties such as carcinogenic and teratogenic. Mitochondria play a key role in cellular homeostasis and keeping a proper energy supply for eukaryotic cells is essential in the fulfillment of the tissues energy-demand. Therefore, interference with mitochondrial function leads to cell death and organ failure. In this work, the effects of DBF on isolated rat liver mitochondria were analyzed. DBF exposure caused a markedly increase in the lag phase that follows depolarization induced by ADP, indicating an effect in the phosphorylative system. This was associated with a dose-dependent decrease in ATPase activity. Moreover, DBF also increased the threshold to the induction of the mitochondrial permeability transition (MPT) by calcium. Pretreatment of mitochondria with DBF also increased the concentration of carboxyatractyloside (CAT) necessary to abolish ADP phosphorylation and to induce the MPT, suggesting that DBF may interfere with mitochondria through an effect on the adenine nucleotide translocase (ANT). By co-immunoprecipitating ANT and Cyclophilin D (CypD) following MPT induction, we observed that in the presence of DBF, the ratio CypD/ANT was decreased. This demonstrates that DBF interferes with the ANT and so prevents CypD binding to the ANT, causing decreased phosphorylative capacity and inhibiting the MPT, which is also reflected by an increase in calcium retention capacity. Clarifying the role of pollutants in some mechanisms of toxicity, such as unbalance of bioenergetics status and mitochondrial function, may help to explain the progressive and chronic evolution of diseases derived from exposure to environmental pollutants.